Anti-oxidant effects of cannabidiol relevant to intracerebral hemorrhage - Yan, Gaili; Zhang, Xiangyu; Li, Hongmin; Guo, Yan; Yong, V. Wee; Xue, Mengzhou (Frontiers in Pharmacology, 2023)
Intracerebral hemorrhage (ICH) is a subtype of stroke with a high mortality rate.Oxidative stress cascades play an important role in brain injury after ICH.Cannabidiol, a major non-psychotropic phytocannabinoids, has drawn increasing interest in recent years as a potential therapeutic intervention for various neuropsychiatric disorders. Here we provide a comprehensive review of the potential therapeutic effects of cannabidiol in countering oxidative stress resulting from ICH.The review elaborates on the various sources of oxidative stress post-ICH, including mitochondrial dysfunction, excitotoxicity, iron toxicity, inflammation, and also highlights cannabidiol's ability to inhibit ROS/RNS generation from these sources.The article also delves into cannabidiol's role in promoting ROS/RNS scavenging through the Nrf2/ARE pathway, detailing both extranuclear and intranuclear regulatory mechanisms. Overall, the review underscores cannabidiol's promising antioxidant effects in the context of ICH and suggests its potential as a therapeutic option.